Sitting on the edge : Modernist design from the collection of Michael & Gabrielle Boyd - Ross, David A.; Boyd, Michael; Betsky, Aaron; Garnier, Philippe; Antonelli, Paola; Ventilla, Melanie (San Francisco : Museum of modern art, 1998)
Sitting on the edge : Modernist design from the collection of Michael & Gabrielle Boyd, San Francisco Museum of Modern Art, San Francisco, November 20, 1998 to February 23, 1999
Aalto, Alvar ; Albers, Josef ; Albini, Franco ; Arström, Folke ; Behrens, Peter ; Bill, Max ; Borsani, Osvaldo ; Breuer, Marcel ; Castiglioni, Achille & Castiglioni, Pier Giacomo ; Castle, Wendell ; Chareau, Pierre ; Chermayeff, Serge ; Colombo, Joe ; Coray, Hans ; Delaunay, Sonia ; Diller, Burgoyne ; Dreyfuss, Henry ; Eames, Charles Eames & Ray ; Goff, Bruce ; Goldman, Paul ; Gray, Eileen ; Harlis, Edelhardt ; Herbst, René ; Hoffmann, Josef ; Jacobsen, Arne ; Jeanneret, Pierre ; Johnson, Dan ; Judd, Donald ; Juhl, Finn ; Kagam, Vladimir ; Kopta, Emry ; Lamers, Michael Boyd & Daven Joy & Eric ; Lassen, Morgens ; Laszlo, Paul ; Le Corbusier ; Lescaze, William ; Loos, Adolf ; Mallet-Stevens, Robert ; McArthur, Albert ; McArthur, Warren ; McLaughlin, John ; Mies van der Rohe, Ludwig ; Mollino, Carlo ; Mouille, Serge ; Müller-Munk, Peter ; Nelson, George ; Neutra, Richard ; Noguchi, Isamu ; Noll, Alexander ; Oud, J.J.K. ; Panton, Verner ; Perriand, Charlotte ; Ponti, Gio ; Prouvé, Jean ; Puiforcat, Jean ; Rietveld, Gerrit ; Rohde, Gilbert ; Saarimen, Eero ; Sapper, Richard ; Scarpa, Carlo ; Schindler, Rudolph ; Stam, Mart ; Stome, Edward Durell ; Stout, Myron ; Teague, Walter Dorwin ; Terragmi, Giuseppe ; Wagenfeld, Wilhelm ; Wagner, Otto ; Weber, Kem ; Wegner, Hans ; Wildenhain, Marguerite ; Wright, Frank Lloyd ; Yanagi, Sori ; Zanuso, Marco ; Zeisel, Eva ; guhl, Willy ; van Doesburg, Theo
boek
Keywords: Boyd, Michael; Boyd, Gabrielle